Enhancing Photovoltaic Performances of Naphthalene‐Based Unfused‐Ring Electron Acceptors upon Regioisomerization. Issue 5 (1st April 2021) - Zhang, Xin; Wei, Yanan; Liu, Xingzheng; Qin, Linqing; Yu, Na; Tang, Zheng; Wei, Zhixiang; Shi, Qinqin; Peng, Aidong; Huang, Hui
Abstract : Isomeric effects play a crucial role in regulating electronic properties, molecular packing, and device performance of organic semiconductors. Herein, a series of unfused‐ring electron acceptor (UREA) regioisomers (NOF‐1, NOF‐2, and NOF‐3), which are constructed using 2, 6‐α‐, 1, 5‐β‐, and 3, 7‐β‐type naphthalene cores, are successfully synthesized and characterized. The regioisomeric effects on geometries, photophysics, electrical properties, molecular packing behaviors, charge transport properties, blend film morphologies, and photovoltaic performance are systematically studied. As a result, the PBDB‐T:NOF‐3‐based device delivers a power conversion efficiency (PCE) of 11.58% due to its more balanced charge mobility, efficient exciton dissociation, less charge recombination, and favorable film morphology. These findings encourage further attention to the regioisomeric effects to design high‐performance UREAs. Abstract : A series of isomeric unfused‐ring electron acceptors (UREAs) involving noncovalent conformational locks are synthesized and characterized. Through the systematic investigation about the regioisomeric effects on the molecular properties, blend morphologies, and device performances, introducing isomeric moieties into molecular design is considered as an effective strategy for exploring more efficient UREAs.